Determinan Kepatuhan Wajib Pajak Orang Pribadi yang Melakukan Pekerjaan Bebas - Armel, R. Septian; Hidayat, Muhammad; Putra, Rudi Syaf (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
This study examines the factors influencing tax compliance among freelance individual taxpayers registered at the Senapelan Primary Tax Office (KPP Pratama Senapelan) in Pekanbaru A quantitative approach using multiple linear regression was employed to measure the effect of each variable. Data were collected through questionnaires distributed to 100 respondents. The findings reveal that only E-Billing implementation and tax sanctions significantly affect compliance. E-Billing has a positive effect, indicating that the more user-friendly the digital system, the higher the taxpayer compliance. Tax sanctions, however, have a significant negative effect, suggesting that overly harsh legal threats may reduce voluntary compliance. Meanwhile, perceived corruption, tax fairness, and socialization showed no significant partial influence. These results suggest that freelance workers are more responsive to technological convenience and proportional sanctions than to normative factors.